polyester fiber
Patent Information
- Application Number
- JP2026016616
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-02-26
- Filing Date
- 2026-02-04
- Publication Date
- 2026-09-07
AI Technical Summary
【0017】 本発明によれば、耐光性に優れるポリエステル繊維を提供することができ、繊維素材の光による退色の抑制が可能となる。
Smart Images

Figure 2026142544000001 
Figure 2026142544000002
Abstract
Description
[Technical Field]
[0001] This invention relates to polyester fibers. More specifically, it relates to polyester fibers with excellent lightfastness. [Background technology]
[0002] Synthetic fibers made from thermoplastic polymers such as polyester and polyamides exhibit excellent mechanical properties and dimensional stability. For this reason, they are widely used not only in clothing but also in interiors, vehicle interiors, and industrial applications, making them extremely valuable in the industrial sector. With the diversification of fiber applications, the required properties have also become diverse, leading to active development of high-performance fibers that improve mechanical properties such as strength, elastic modulus, and abrasion resistance, as well as functional properties such as antistatic properties, high colorfastness, and texture. However, with the growing concern for environmental issues in recent years, fiber development must not only pursue functionality but also be environmentally friendly in order to realize a sustainable society.
[0003] Reducing the environmental impact of synthetic fibers includes using recycled and biomass raw materials, reducing utility and energy consumption during the manufacturing process, and recycling products. Among these, extending the lifespan of fibers is considered one of the ultimate environmentally conscious measures because it effectively reduces the environmental impact of the entire manufacturing process by conserving resources, lowering manufacturing costs, and reducing waste.
[0004] From the perspective of extending the lifespan of fibers, fiber materials are required to possess not only mechanical durability such as strength and abrasion resistance to withstand long-term use, but also robustness to maintain the quality of the fiber material.
[0005] Colorfastness refers to the durability of dyed textile materials against discoloration such as fading and color transfer. The degree of discoloration of textile materials that discolor due to washing, friction, light, etc., is evaluated on a scale. Among these, discoloration of textile materials due to sunlight, specifically ultraviolet rays, is the most unavoidable discoloration phenomenon in daily life. Since the aesthetic appeal of discolored textile materials is significantly impaired, consumers tend to discard textile materials, making it a challenge in extending the lifespan of textiles. For this reason, as a measure to impart lightfastness to textiles, highly lightfast dyes that are resistant to photodegradation by ultraviolet rays have been used to suppress discoloration of textiles. However, limiting the types of dyes limits the range of colors available for textile materials and leads to limitations in their applications, which is undesirable. Therefore, there is a desire to suppress discoloration of textiles without limiting the types of dyes, and various technologies related to improving the lightfastness of textiles have been proposed.
[0006] Patent Document 1 proposes a copolymerized polyester fiber having excellent dyeability and lightfastness by specifying the polymerization amount of 1,2-propanediol, which is a copolymerization component in polyester fibers.
[0007] Patent Document 2 proposes a technology to improve the light resistance of polyester fibers by adding a benzotriazole-based ultraviolet absorber to bisphenol A ethylene oxide-containing polyester fibers.
[0008] Patent Document 3 proposes a technology that improves light resistance by adding an ultraviolet absorber or light stabilizer to a sheet made of polyester. [Prior art documents] [Patent Documents]
[0009] [Patent Document 1] Japanese Patent Publication No. 2023-184004 [Patent Document 2] Japanese Patent Application Publication No. 7-189031 [Patent Document 3] Japanese Patent Publication No. 2000-144583 [Overview of the project] [Problems that the invention aims to solve]
[0010] Patent Document 1 proposes a polyester fiber that exhibits high color development by increasing dye penetration in the amorphous region while maintaining lightfastness by limiting the copolymerization amount of 1,2-propanediol to a small amount of 0.13 to 5 mol%. However, this technology achieves improved lightfastness by limiting the amount of a specific copolymerization component added, and does not solve the root cause of the decrease in lightfastness caused by the copolymerization component, so the effect may be limited. Furthermore, since it is based on the premise of containing a specific copolymerization component, there were issues such as difficulty in applying it to other polyester fibers.
[0011] Patent Document 2 suggests that by adding a benzotriazole-based UV absorber, it may be possible to reduce the amount of UV absorbed by polyester fibers and improve their lightfastness by absorbing UV light with a wavelength of 350 nm or higher. This technology may suppress the photodegradation of dyes, which occurs when dyes are photodegraded due to the absorption of light energy from UV light, by reducing the amount of UV absorbed.
[0012] However, a disadvantage of using additives is that they can leach out of the fiber material over time, making it difficult to reduce the amount of UV absorbed by the fiber and thus hindering the prevention of fiber fading. In addition, some benzotriazole-based UV absorbers are known to be difficult to decompose and bioaccumulative, which may limit their range of applications.
[0013] Patent Document 3 proposes that in the case of UV absorbers, lightfastness can be improved by converting light with a wavelength of 400 nm or less into thermal energy, while in the case of light stabilizers, it can be improved by preventing photodegradation through antioxidant effects or radical scavenging effects. In this technology, in the case of UV absorbers, it is possible to suppress the photodegradation of dyes by reducing the amount of UV absorbed, while in the case of light stabilizers, it is possible to suppress the photodegradation of dyes by acting on the dye or reaction intermediate.
[0014] However, some of the benzotriazole-based and benzophenone-based ultraviolet absorbers, or phenol-based light stabilizers used in Patent Document 3 have potential adverse effects on the human body, so the scope of applications may be limited.
[0015] The present invention aims to solve the above problems, and an object of the present invention is to provide a polyester fiber that improves the light resistance of the polyester fiber and has excellent light resistance over a long period of time. [Means for Solving the Problem]
[0016] In order to solve the above problems, the present invention has the following constitution. (1) A polyester fiber having a carbon radical content of 2.0E+14 spins / g or less (2) The polyester fiber according to claim 1, which is a polyester containing a copolymerization component [Effect of the Invention]
[0017] According to the present invention, a polyester fiber excellent in light resistance can be provided, and the fading of a fiber material caused by light can be suppressed. [Mode for Carrying Out the Invention]
[0018] For the polyester constituting the polyester fiber in the present invention, any polyester such as polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, and polylactic acid can be used. Among these, polycondensation polymers such as polyethylene terephthalate, polytrimethylene terephthalate, and polybutylene terephthalate have high melting points, and a melting point of 165°C or higher is preferable because it provides good heat resistance. In particular, polyethylene terephthalate is more preferable in view of good moldability and spinnability, excellent balance of mechanical properties, durability, and dimensional stability as a fiber material, and further from the viewpoint of easy recycling in the end. In addition, as described later, the use of a copolyester is also a preferred embodiment of the present invention.
[0019] Amid growing attention to environmental issues, the use of plant-derived biopolymers and recycled polymers in the present invention is also favorable from the perspective of reducing environmental load. The polymer used in the above-described present invention can employ a recycled polymer reclaimed by any of chemical recycling, material recycling, and thermal recycling methods. The polymer may contain various additives such as inorganic substances including titanium oxide, silica, and barium oxide, colorants including carbon black, dyes and pigments, flame retardants, fluorescent brighteners, antioxidants, or ultraviolet absorbers, as long as the effects of the present invention are not impaired.
[0020] The inventors of the present invention have conducted intensive studies on the suppression of discoloration caused by ultraviolet rays in clothing materials and the like, which have been conventionally studied and technically proposed mainly for improving the light resistance of dyes, and have found that carbon radicals within fibers, which have not attracted attention until now, are closely involved in the discoloration of polyester fibers.
[0021] That is, the discoloration of polyester fibers is a phenomenon in which after dye radicals are generated due to the absorption of light energy from ultraviolet rays by the dye, chain chemical structural changes occur, and the visible light absorbance of the dye changes due to changes in the conjugated structure of the dye or decomposition thereof. The inventors have discovered that carbon radicals within fibers are the starting point of the discoloration of polyester fibers, where they promote the generation of dye radicals through radical transfer to the dye. The radical transfer of the carbon radicals to the dye is likely to occur when receiving stimuli such as light, heat, and chemical reactions, and specifically, it is caused by high-order processing involving heating such as dyeing and heat setting, and ultraviolet irradiation to fiber materials. Based on the discovery of the above phenomenon, by controlling the amount of carbon radicals in polyester fibers, radical transfer to dyes and transformation of dyes are fundamentally suppressed, and the light resistance of the polyester fibers themselves is improved, thus making it possible to significantly suppress discoloration caused by ultraviolet rays and the like.
[0022] Therefore, the polyester fibers of the present invention can suppress the formation of dye-modified products whose visible light absorbance differs from that of the original dye by controlling the amount of carbon radicals. As a result, it is difficult to observe color unevenness between areas irradiated with ultraviolet light and areas that are not irradiated with ultraviolet light, and the color difference is less than 2.0.
[0023] The color difference referred to here is determined as follows: For a polyester fiber, L*, a*, and b* are measured at five locations each in an arbitrary non-UV-irradiated area and L*', a*', and b*' at an arbitrary UV-irradiated area using a spectrophotometer and a colorimetric light source. Then, ΔE is calculated using the following formula, and the color difference is obtained by rounding the average value to two decimal places. ΔE={(L*-L*') 2 +(a*-a*') 2 +(b*-b*') 2} 1 / 2 Average values of color measurements taken from areas of polyester fiber not exposed to UV light: L*, a*, b* Average values of color measurements taken at UV-irradiated areas of polyester fibers: L*', a*', b*' A color difference of less than 2.0 is preferable because it indicates a low presence of dye-modified substances due to UV irradiation in the polyester fibers, and therefore no color changes caused by these substances. A color difference of less than 1.5 is even more preferable because the color unevenness is barely perceptible to the human eye, and a color difference of less than 1.0 is even more preferable because the color unevenness is completely imperceptible to the human eye, providing a high-quality fiber material with superior appearance.
[0024] Discoloration of polyester fibers occurs most significantly in the fiber surface, which has a large surface area for receiving ultraviolet light, and therefore a large number of dye-modified substances are present in the fiber surface. The polyester fiber of the present invention makes it possible to uniformly improve the light resistance of the entire fiber, regardless of whether it is in the interior or surface, by controlling the amount of carbon radicals. As a result, even in the fiber surface, there is almost no decomposition of dye before and after ultraviolet irradiation, and the dye content in the fiber surface is 20% or more.
[0025] The dye abundance referred to here is determined as follows: Polyester fibers were subjected to time-of-flight secondary ion mass spectrometry (TOF-SIMS), which is capable of measuring the mass spectrum of the fiber surface. After identifying ions originating from the polyester skeleton and ions originating from the dye structure from the obtained mass spectrum, the dye abundance before and after ultraviolet irradiation was calculated using the following formula. Dye abundance (%) = {(Dye peak intensity after UV irradiation / Polyester peak intensity after UV irradiation) / (Dye peak intensity before UV irradiation / Polyester peak intensity before UV irradiation)} × 100 The detailed measurement conditions are as described in the Examples section, and the fiber surface layer is defined as the area within 3 nm from the fiber surface that can be analyzed by TOF-SIMS.
[0026] If the dye content on the fiber surface is 20% or more, it means that there is enough undegraded dye on the fiber surface to give the fiber material a color development comparable to that before UV irradiation, and this can be cited as a preferred range from the perspective of the present invention. Furthermore, from this viewpoint, if the dye content is 25% or more, the fiber material will hardly show any fading, so this is more preferable, and if the dye content is 30% or more, the fiber material will not show any fading at all, and a high-quality fiber material with an excellent appearance on the fiber surface can be provided, so this is particularly preferable.
[0027] In this invention, a carbon radical refers to a carbon atom of any of the primary, secondary, tertiary, or quaternary carbon atoms that has unpaired electrons and is generated by stimuli such as light, heat, or chemical reactions. The carbon atom generated by the carbon radical may be any of the constituent components of polyester fibers, such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, terephthalic acid, vinyl acetate, lactic acid, etc., or it may be a carbon atom of a dye in the polyester fiber.
[0028] In this invention, carbon radicals may be generated not only by light stimulation through ultraviolet absorption, but also by heat or chemical reactions, and may be generated at any time. Specifically, examples of generation times include the polymerization reaction of polyester, the drying process of chips, the melting process in melt spinning, and the heat setting, dyeing, and washing processes of fabrics in advanced processing.
[0029] The carbon radical amount in this invention refers to the number of carbon radicals present per unit weight of polyester fiber. The carbon radical amount, a key requirement in this invention, can be determined by subjecting the polyester fiber to electron spin resonance (ESR) measurement, identifying the signal originating from carbon radicals in the resulting differential curve, integrating the differential curve twice to obtain the signal intensity of carbon radicals, calculating the number of carbon radicals based on the signal intensity of a standard sample with a known radical amount (in this invention, ion-implanted polyethylene film is used), and dividing by the weight of the sample being measured. Detailed ESR measurement conditions are described in the Examples section.
[0030] The polyester fiber of the present invention has a carbon radical content of 2.0E+14 atoms / g (2.0 × 10⁻¹⁴). 14 It is important that the amount of carbon radicals is 2.0E+14 / g or less. When the amount of carbon radicals in polyester fibers is 2.0E+14 / g or less, radical transfer to the dye when exposed to stimuli such as light, heat, or chemical reactions is suppressed, and the amount of dye radicals generated is reduced, thereby preventing fading of the polyester fibers. From this viewpoint, if the amount of carbon radicals is 1.6E+14 / g or less, the amount of carbon radicals contributing to the photodegradation of the dye can be further reduced, making it suitable for use in clothing such as coats that are directly exposed to ultraviolet rays, and is therefore more preferable. Furthermore, if the amount of carbon radicals is 1.3E+14 / g or less, it can be suitable for use in industrial applications such as automotive interior materials, where even higher light resistance than that required for clothing is needed.
[0031] The effects of the present invention are more effectively achieved with polyesters containing copolymer components, and therefore, preferred embodiments of the present invention can be listed.
[0032] In other words, when polyester fibers contain copolymer components, the orientation of molecular chains is inhibited, crystal formation in the fibers is suppressed, and the proportion of amorphous structures in the fibers can be increased, thus increasing the amount of dye that can be absorbed during dyeing. For this reason, copolymerized polyester fibers containing copolymer components have improved dyeability and better color development, such as depth of color, when subjected to the same dyeing process, compared to polyester fibers without copolymer components. However, in the case of conventional technology, the above phenomenon causes the dye to decompose due to carbon radicals, making the fabric prone to fading. Furthermore, in polyester fibers containing copolymer components, the dye that is sufficiently absorbed in the initial stages becomes inactive, which can sometimes lead to more pronounced fading of the fabric.
[0033] To address this challenge, conventional methods often utilize UV absorbers or light stabilizers to suppress dye degradation. However, this does not reduce carbon radicals, which are the root cause of fading, and combined with the initial high color development, fading becomes more pronounced. Furthermore, the need to add UV absorbers or light stabilizers other than the dye can unnecessarily complicate the process, such as the method of addition and process temperature control.
[0034] In this invention, the key is to improve the lightfastness of the fibers by reducing the amount of carbon radicals, which are the root cause of fading. By introducing copolymer components, the dye is sufficiently absorbed into the fiber structure, allowing for easy dyeing to the interior of the fiber, and increasing the amount of dye absorbed even at the microscopic level. As a result, a large amount of undegraded dye remains compared to the dye decomposed by the transfer of carbon radicals (dye-modified products), and the polyester fiber as a whole exhibits the same color development as before UV irradiation, making it possible to produce a highly colored polyester fiber with excellent lightfastness.
[0035] In this context, copolymer components refer to compounds other than the repeating units in the primary structure of polyester fibers. For example, in the case of polylactic acid, which consists of one repeating unit, it refers to compounds other than lactic acid, and in the case of polyethylene terephthalate, which consists of two main repeating units, it refers to compounds other than the polycondensate of terephthalic acid and ethylene glycol.
[0036] The copolymer component of the present invention is preferably one that inhibits the formation of fiber structure in polyester fibers and increases the proportion of amorphous structures. It is preferably selected from dicarboxylic acids and their derivatives, such as phthalic acid, isophthalic acid, cyclic carboxylic acid, 5-sodium sulfisoisophthalic acid, or diols and their derivatives, such as trimethylene glycol, tetramethylene glycol, polyethylene glycol, bisphenol. Furthermore, if the copolymer component is isophthalic acid, bisphenol A ethylene oxide adduct, or both, it is possible to impart flexibility to the molecular chains and significantly increase the proportion of amorphous structures in the fibers while maintaining normal fluidity. In addition, a large number of undegraded dyes remain compared to the dyes degraded by carbon radical transfer, and the overall color development of the polyester fiber appears more remarkably similar to that before UV irradiation. Therefore, this can be cited as a particularly preferred configuration.
[0037] There are no particular restrictions on the timing of adding the copolymerization component of the present invention; it may be added at any time, such as during polymerization or spinning.
[0038] Next, the physical properties of the polyester fiber of the present invention will be described.
[0039] The fineness of the polyester fiber of the present invention is not particularly limited and can be appropriately selected according to the application and required characteristics, but 5 dtex to 300 dtex is preferred. Fineness in the present invention refers to the value measured by the method described in the Examples section. A fineness of 5 dtex or more in the polyester fiber is preferred because, due to the large fiber diameter, a large number of undegraded dyes can exist in the inner layer of the fiber relative to the degraded dyes in the surface layer by ultraviolet light. It is also preferred because it ensures good process passability, suppression of fuzz generation during use, and excellent durability, thus guaranteeing fiber strength suitable for use as a raw material for clothing. From this viewpoint, a fineness of 10 dtex or more in the polyester is more preferred, and 15 dtex or more is even more preferred. On the other hand, a fineness of 300 dtex or less in the polyester fiber is preferred because, due to the small fiber diameter, the specific surface area of the fiber in the fiber material increases, making it possible to increase the reflected light of irradiated ultraviolet light, thereby reducing the amount of ultraviolet light absorbed by the dye and polyester in the fiber. It is also preferred because it does not impair the flexibility of the fiber and fiber structure. From this perspective, the fineness of the polyester is more preferably 200 dtex or less, and even more preferably 150 dtex or less.
[0040] The strength of the polyester fiber of the present invention is preferably adjusted according to the application and required characteristics by the manufacturing method described later. Here, the strength of the present invention refers to the value measured by the method described in the Examples section. The higher the strength, the better it can withstand post-processing steps and actual use, and the less likely it is to break. On the other hand, since the polyester fiber of the present invention is manufactured using a general spinning process, there is an upper limit to the feasible strength, and considering the handling of the fiber, the strength of the fiber of the present invention is preferably between 0.3 cN / dtex and 10.0 cN / dtex. Furthermore, the polyester fiber of the present invention is preferably adjusted according to the elongation required for its use, and when used in clothing applications, it is particularly preferable to have a strength between 0.5 cN / dtex and 5.0 cN / dtex.
[0041] The elongation of the polyester fiber of the present invention is preferably adjusted according to the application and required characteristics by the manufacturing method described later. Here, the elongation of the present invention refers to the value measured by the method described in the Examples section. The higher the elongation, the less likely the fiber is to break even when subjected to rapid deformation. On the other hand, since elongation deformation during molding can sometimes make the properties of the textile product unstable, considering the handling of the fiber, the elongation of the fiber of the present invention is more preferably 30% to 60%. Furthermore, the polyester fiber of the present invention is preferably adjusted according to the elongation required for its use. When used in clothing applications, it is particularly preferable to adjust it to 30% to 50%, and when used in non-clothing applications, it is preferable to adjust it to 20% to 40%.
[0042] The polyester fiber of the present invention may take any form, such as monofilament, multifilament, or staple, and the cross-sectional shape may be appropriately selected according to the application and required characteristics. It may have a circular cross-section or a non-circular cross-section. Furthermore, utilizing the high color development and lightfastness of the present invention, it is also preferable to create a composite fiber by combining it with other components, from the viewpoint of combining aesthetics and functionality.
[0043] The polyester fibers of the present invention can be processed, such as false twisting, in the same way as general fibers, and can be handled in the same way as general fibers in weaving and knitting. As woven or knitted fabrics, there are no special restrictions on their form, and they may be woven fabrics, knitted fabrics, or pile fabrics according to known methods. Furthermore, the present invention may be any weave or knit structure, and plain weave, twill weave, satin weave or variations thereof, as well as warp knitting, weft knitting, circular knitting, lace knitting or variations thereof can be suitably employed. In addition, when forming a fiber structure, it may be combined with other fibers by interweaving or interknitting, or it may be a fiber structure made by blending with other fibers into a yarn.
[0044] Next, an example of a method for producing polyester fibers according to the present invention will be described in detail.
[0045] The polyester fibers of the present invention preferably contain an ultraviolet absorber for the purpose of improving light resistance. The ultraviolet absorber absorbs ultraviolet light irradiated onto the fiber material, reducing the amount of ultraviolet light absorbed by the fiber and dye. Therefore, by adding an ultraviolet absorber to the polyester fibers, radical transfer from the polyester fibers to the dye caused by ultraviolet irradiation of the fiber material is suppressed, and the light resistance of the polyester fibers is further improved.
[0046] Examples of ultraviolet absorbers in the present invention include benzotriazine-based, benzotriazole-based, benzophenol-based, and salicylic acid-based compounds. Among these, benzotriazole-based ultraviolet absorbers are particularly suitable because, when added during melting, they exhibit excellent heat resistance, suppressing the formation of thermal decomposition products, thus preventing discoloration of polyester fibers and a decrease in ultraviolet absorption function. Furthermore, high molecular weight benzotriazole-based ultraviolet absorbers are particularly suitable because they have a high melting point and higher thermal stability.
[0047] In this invention, the UV absorber content is preferably between 0.01 wt% and 4.5 wt%. If the UV absorber content is 0.01 wt% or more, it absorbs ultraviolet light irradiated onto the fiber material, suppressing radical transfer from polyester fibers to dyes, and enabling high lightfastness of polyester fibers. Furthermore, if the UV absorber content is 4.5 wt% or less, the decrease in the melt viscosity of the polymer due to an increase in the amount of UV absorber is suppressed, resulting in stable discharge from the spinneret during spinning and excellent spinnability, which is preferable. In addition, by suppressing discoloration of polyester fibers due to the UV absorber, there are no restrictions on color range in clothing applications.
[0048] The method for producing the polyester fibers of the present invention is not particularly limited, and examples include wet and wet-dry solution spinning methods, as well as melt-blown and spunbond methods suitable for obtaining sheet-like fiber structures. However, from the viewpoint of increasing productivity, melt spinning is preferred. The melt spinning method will be described below as an example.
[0049] The spinning temperature for the polyester fibers of the present invention is preferably set to a temperature at which the polymer used exhibits fluidity. This fluidity temperature varies depending on the molecular weight, but it is preferable to set it between the melting point of the polymer and the melting point + 60°C, as this allows for stable production.
[0050] The discharge rate when spinning the polyester fibers of the present invention can be stably discharged within a range of 0.1 g / min / hole to 20.0 g / min / hole per discharge hole. In this case, it is preferable to determine the discharge rate according to the desired fiber diameter, taking into consideration winding conditions, stretching ratio, etc.
[0051] The molten polymer flow discharged from the discharge port is cooled and solidified, then focused by the application of an oil or the like, and taken up by a roller with a specified peripheral speed. Here, the take-up speed is determined by the discharge volume and the desired fiber diameter. In this invention, from the viewpoint of stably producing polyester fibers, the roller take-up speed is preferably set to about 500 m / min to 6000 m / min, and can be changed depending on the physical properties of the polymer and the intended use of the fibers.
[0052] From the viewpoint of improving the mechanical properties of spun polyester fibers by promoting uniaxial orientation of the fibers, it is preferable to stretch them. For example, in a stretcher consisting of one or more rollers, if the fibers are made of a polymer that is generally melt-spinnable and exhibits thermoplasticity, the fibers are stretched smoothly in the axial direction and then heat-set and wound up by the peripheral speed ratio of a first roller set to a temperature above the glass transition temperature but below the melting point and a second roller set to a temperature equivalent to the crystallization temperature. In the case of polymers that do not exhibit glass transition, the dynamic viscoelasticity (tanδ) of the polyester fiber can be measured, and a temperature above the peak temperature on the high-temperature side of the obtained tanδ can be selected as the preheating temperature.
[0053] Furthermore, regarding the stretching process, it is possible to stretch the spun polyester fibers after winding them up, or to stretch them immediately after spinning without winding them up first. However, from the perspective of enhancing wearability by creating a complex texture and feel in the fabric by changing each individual fiber into a different, non-uniform shape, it is more preferable to perform yarn processing that involves stretching.
[0054] While the yarn processing method is not particularly limited to known yarn processing techniques such as false twisting and uneven stretching, false twisting is preferable from the standpoint of imparting crimp to the yarn bundle and providing a fiber material with good tactile quality and texture.
[0055] While there are no particular limitations on the method used for false twisting, as long as it is a method commonly used for polyester, it is preferable to use a friction false twisting machine with discs or belts for productivity reasons.
[0056] The polyester fibers of the present invention may be dyed in either the fiber state or the woven or knitted state. However, dyeing in the woven or knitted state is preferable to dyeing in the fiber state because it offers superior production efficiency and allows for a wide range of colors to meet customer demands.
[0057] In the dyeing process of the present invention, disperse dyes are preferred because they offer a wide range of color options and are suitable for application to polyester fibers.
[0058] The dyeing method in the present invention is not particularly limited, and can suitably employ cheese dyeing machines, jet dyeing machines, drum dyeing machines, beam dyeing machines, jiggers, high-pressure jiggers, etc., according to known methods.
[0059] In this invention, there are no particular restrictions on dye concentration or dyeing temperature, and known methods can be suitably employed. Furthermore, if necessary, it is preferable to perform a scouring treatment before dyeing.
[0060] In this invention, it is preferable to perform reductive washing after dyeing. Conventionally, reductive washing is a process aimed at improving the fastness of fibers by reducing and decomposing unfixed dyes that have not adhered to the inside of the fibers and washing them. However, in this invention, since the radical scavenging effect of the reducing agent used in reductive washing has been discovered, reductive washing is performed with the aim of reducing the amount of carbon radicals in the fibers. This is because the anions of the reducing agent generated by ionization in the reducing solution are electrically attracted to and react with carbon radicals in the polyester fibers, thereby scavenging the radicals. By adding a reducing agent, it is possible to control the amount of carbon radicals in the polyester fibers. For this reason, in this invention, reductive washing is performed not only for the reductive decomposition of dyes but also for the purpose of controlling the amount of carbon radicals in the fibers, and it is preferable to perform reductive washing because it enables improved lightfastness.
[0061] In the present invention, by adjusting the reduction washing conditions such as the reducing agent concentration, reduction washing temperature, reduction washing time, and reduction washing bath ratio, it is possible to reduce the amount of carbon radicals in polyester fibers to 2.0E+14 atoms / g or less, so that the reducing agent can sufficiently capture carbon radicals in polyester fibers.
[0062] In the reduction washing method of the present invention, it is preferable to set the concentration of the reducing agent that captures carbon radicals to 6.0%owf or more and 65.0%owf or less, so that the amount of carbon radicals in the polyester fibers is 2.0E+14 / g or less. However, %owf refers to the amount of reducing agent added relative to the weight of the polyester fibers to be reduced and washed. A reducing agent concentration of 6.0%owf or more is preferable because it can capture enough carbon radicals in the polyester fibers to prevent fading due to ultraviolet light. From this viewpoint, it is more preferable to have a concentration of 10.0%owf or more, and even more preferable to have a concentration of 20.0%owf or more. On the other hand, a reducing agent concentration of 65.0%owf or less is preferable because it prevents a decrease in the reducing power of the reducing agent that occurs when the reducing solution is acidic, and it is possible to prevent a decrease in the carbon radical capture ability by keeping the solution alkaline. From this viewpoint, it is more preferable to have a concentration of 60.0%owf or more, and even more preferable to have a concentration of 55.0%owf or more.
[0063] In the reduction washing method of the present invention, it is preferable to set the reduction washing temperature to 45°C or higher and 100°C or lower. A reduction washing temperature of 45°C or higher is preferable because it activates the mobility of the reducing agent in the reduction solution, making it possible to capture carbon radicals of polyester fibers. From this viewpoint, a reduction washing temperature of 60°C or higher is more preferable because it further activates the reducing agent. On the other hand, a reduction washing temperature of 100°C or lower is preferable because it can suppress the heat shrinkage rate to a level suitable for the use of polyester fibers as a fiber material, and a temperature of 95°C or lower is even more preferable.
[0064] In the reduction cleaning process of the present invention, it is preferable to set the reduction cleaning time to 5 minutes or more and 60 minutes or less. A reduction cleaning time of 5 minutes or more is preferable because it provides sufficient time for the reducing agent to capture carbon radicals in the polyester fibers. From this viewpoint, a reduction cleaning time of 10 minutes or more is more preferable. On the other hand, a reduction cleaning time of 60 minutes or less is preferable because it is possible to prevent the deterioration of mechanical properties associated with hydrolysis of the polyester fibers in the alkaline solution, and a time of 50 minutes or less is even more preferable.
[0065] In the reduction washing method of the present invention, the reduction washing bath ratio (weight ratio of the reducing solution to the weight of the fiber) is preferably 1:5 or higher. A reduction washing bath ratio of 1:5 or higher is preferable because it allows the reducing solution to penetrate sufficiently into the polyester fibers and capture carbon radicals in the polyester fibers evenly and uniformly. From this viewpoint, a reduction washing bath ratio of 1:10 or higher is more preferable. On the other hand, there is no particular upper limit to the reduction washing bath ratio and it is determined by the equipment used for reduction washing.
[0066] In the reductive washing method of the present invention, it is preferable to use a reducing solution consisting of a reducing agent and an alkali. The reducing agent used is not particularly limited as long as it has reducing power capable of reducing and decomposing dyes and capturing carbon radicals, but hydrosulfite is preferred as it is a versatile reducing agent with excellent reducing power. The alkali used is not particularly limited as long as it can maintain the pH of the reducing solution between 7 and 14 so that the reducing agent can exert its effect, and a weak alkali such as sodium carbonate may be used, but a strong alkali such as sodium hydroxide is preferred because it can adjust the pH to the desired level with the addition of a small amount.
[0067] The reduction cleaning method in the present invention is not particularly limited and can be carried out according to known methods. Furthermore, there are no particular limitations regarding the reduction cleaning time, temperature, or bath ratio, and known methods can be suitably employed. [Examples]
[0068] The polyester fiber of the present invention will be described in detail below with reference to examples. The following evaluations were performed on the examples and comparative examples.
[0069] A. Fineness Using an electric measuring machine YC-1 manufactured by Intec Co., Ltd., the weight of 100m of fiber was measured, and this value was multiplied by 100 to calculate the fineness (dtex). This measurement was repeated 10 times, and the average value was rounded to two decimal places to determine the fineness (dtex).
[0070] B. Mechanical properties of fibers Using an Orientec Tensilon UCT-100 tensile testing machine, the stress-strain curve of the fiber was measured under the conditions of a sample length of 20 cm and a tensile speed of 20 cm / min. The load at fracture was read, and the fracture strength was calculated by dividing that load by the fineness. The strain at fracture was read, and the value obtained by dividing it by the sample length and multiplying by 100 was calculated to calculate the elongation at fracture. This operation was repeated five times for each level, and the average value of the obtained results was calculated and rounded to two decimal places to represent the strength (cN / dtex) or elongation (%).
[0071] C. Carbon radical amount To the tubular knitted polyester fibers obtained in the Examples and Comparative Examples, 1.0 g / L of sodium carbonate and 1.0 g / L of Meisei Chemical Industry Co., Ltd.'s surfactant "Granup" US-20 were added. After removing the spinning oil by scouring, the material was rinsed with running water for 30 minutes and dried in a 60°C hot air dryer for 60 minutes. After drying, the tubular knitted material was subjected to an intermediate setting at 170°C for 1 minute. Then, 3% by weight of Dianix BLUE S-2G 200% manufactured by Dystar Co., Ltd. was added as a blue disperse dye, and 1 g / L of Ionet RAP-250 manufactured by Sanyo Chemical Industries, Ltd. was added as a uniforming agent. The dye solution was adjusted to pH 5.0, and the material was dyed at 130°C for 30 minutes with a bath ratio of 1:40. After that, it was rinsed with running water for 30 minutes and dried in a 60°C hot air dryer for 30 minutes. The dyed tubular knitted fabric was reductively washed for 20 minutes at 80°C in an aqueous solution containing hydrosulfite, 0.7 g / L sodium hydroxide, and 0.5 g / L of Meisei Chemical Industry Co., Ltd.'s surfactant "Granup" US-20 at a predetermined concentration, in a bath ratio of 1:40. After that, it was rinsed with running water for 30 minutes, dried in a hot air dryer at 60°C for 60 minutes, and then finished setting at 170°C for 1 minute. Subsequently, the tubular knitted material, after reduction washing, was cut to approximately 10 mm x 30 mm and packed into a quartz tube with an inner diameter of 3 mm. Electron spin resonance (ESR) measurements were performed using a BRUKER EMXplus electron spin resonance spectrometer at room temperature, with a central magnetic field of approximately 3516 G, microwave frequency of 9.86 GHz, 0.25 mW, modulation of 100 kHz, and 5 G. After identifying the signal originating from carbon radicals in the obtained differential curve, the differential curve was integrated twice to obtain the signal intensity of the carbon radicals. The number of carbon radicals was then calculated based on the signal intensity of a standard sample with a known radical amount (in this invention, ion-implanted polyethylene film was used), and the amount of radicals was determined by dividing this by the weight of the measured sample.
[0072] D. Color difference Using the tube-knitted fabric after reduction cleaning obtained in Section C above as a sample, a grade 4 light fastness test was carried out in accordance with the 3rd exposure method of JIS L0842 2021, and L*, a* and b* were measured using a spectrophotometer CM-700d / 600d and a colorimetric light source D65. Color measurement was carried out at 5 locations each on samples before and after the 3rd exposure method test of JIS L0842 2021, ΔE was calculated from the average value by the following calculation formula, and the value rounded to two decimal places was taken as the color difference. ΔE = {(L*-L*' ) 2 +(a*-a*' ) 2 +(b*-b*' ) 2} 1 / 2 Average value of color measurement values at non-ultraviolet irradiated locations of polyester fiber: L*, a*, b* Average value of color measurement values at ultraviolet irradiated locations of polyester fiber: L*', a*', b*'.
[0073] E. Dye existence rate on fiber surface layer Using the tube-knitted fabric before and after the grade 4 light fastness test of the 3rd exposure method of JIS L0842 2021 obtained in Section D above as samples, the samples were subjected to time-of-flight secondary ion mass spectrometry (TOF-SIMS) using a time-of-flight secondary ion mass spectrometer TOF.SIMS5 manufactured by IONTOF, and phthalic acid-based ions derived from the polyester skeleton (m / z 191.04, structural formula C 10 H7O4 - ) and ions derived from the dye structure (m / z 624.08, structural formula C 23 H 25 N6O 10 Br - ) were identified, then the peak intensity of each spectrum was observed, and the dye existence rate before and after ultraviolet irradiation was calculated using the following formula Dye existence rate (%) = {(dye peak intensity after ultraviolet irradiation / polyester peak intensity after ultraviolet irradiation) / (dye peak intensity before ultraviolet irradiation / polyester peak intensity before ultraviolet irradiation)}×100 to calculate the dye existence rate before and after ultraviolet irradiation.
[0074] F. Light fastness The tubular knit fabric obtained by reduction washing according to item C above was used as a sample, and a lightfastness test of grade 4 was conducted in accordance with JIS L0842 2021, method 3 of exposure. The degree of fading compared to the blue scale of the standard sample was graded in two stages, grade 4 or higher, or below grade 4, by a majority vote of five inspectors with more than five years of experience in quality judgment. Lightfastness was evaluated using the sample obtained in C above as the initial sample, after 10 wash cycles (conditions in accordance with JIS L0844 2011 A-2) and 100 wash cycles.
[0075] [Example 1] Polyethylene terephthalate (copolymerized PET), copolymerized with 7.0 mol% isophthalic acid and 4.0 mol% 2,2-bis[4-(2-hydroxyethoxy)phenyl]propane, was melted at 290°C and extruded at a rate of 42.0 g / min from a spinneret (extrusion hole diameter 0.23 mm, extrusion hole length 0.30 mm, number of holes 36, round holes). After cooling and solidifying, an oil was applied to the extruded polymer stream, and the stream was wound at a spinning speed of 2500 m / min. Polyester fibers with 88 dtex-36 filaments were produced by stretching between rollers heated to 90°C and 130°C.
[0076] From the obtained drawn yarn, tubular knitted fabric was produced using an Eiko Sangyo NCR-BL circular knitting machine (3.5 inches (8.9 cm) diameter, 27 gauge). After dyeing, reduction washing was carried out using a Techsam Giken UR-MINI-COLOR mini-color dyeing machine at a temperature of 80°C, for 20 minutes, with a heating rate of 2°C / min and a bath ratio of 1:20, at a hydrosulfite concentration of 12.5% owf. During reduction washing, the reducing solution and the tubular knitted fabric were constantly stirred in the mini-color pot. The fiber properties and fabric properties of the obtained drawn yarn are shown in Table 1.
[0077] To capture carbon radicals in polyester fibers, the hydrosulfite concentration was set to 25% owf during reductive washing, resulting in a carbon radical count of 1.2E+14 / g in the fibers. In Example 1, dye degradation due to radical transition was suppressed, and the lightfastness evaluation results were good, with a color difference of 1.0, a dye presence on the fiber surface of 33.3% owf, and a lightfastness rating of 4 or higher.
[0078] [Examples 2, 3, Comparative Examples 1-3] To alter the amount of carbon radicals in the fibers, the method described in Example 1 was modified by omitting the reduction step (Comparative Example 1), changing the reducing agent concentration to 4.0% owf (Comparative Example 2), 10.0% owf (Example 2), 62.5% owf (Example 3), and 75.0% owf (Comparative Example 3), while other conditions were carried out according to Example 1. The results of these lightfastness evaluations are shown in Table 1. Examples 2 and 3 showed excellent lightfastness by controlling the amount of carbon radicals in the substrate, similar to Example 1.
[0079] On the other hand, in Comparative Examples 1 and 2, the capture of carbon radicals in the reducing solution was insufficient, resulting in a carbon radical count of 2.0E+14 / g or more, and thus poor lightfastness. Conversely, in Comparative Example 3, where the amount of reducing agent in the reducing solution was excessive and the pH of the reducing solution was lowered to the acidic side, the carbon radical capture ability of the reducing agent decreased, resulting in a carbon radical count of 2.0E+14 / g or more in the substrate, and thus poor lightfastness, similar to Comparative Examples 1 and 2.
[0080] [Examples 4 and 5] The procedure was carried out in the same manner as in Example 1, except that the polymer was changed to polyethylene terephthalate with an isophthalic acid copolymer content of 1.8 mol% and a 2,2-bis[4-(2-hydroxyethoxy)phenyl]propane copolymer content of 1.0 mol% (using chips mixed in chip form with a blending ratio of 25% by weight of polyethylene terephthalate copolymerized with 7.0 mol% isophthalic acid and 4.0 mol% of 2,2-bis[4-(2-hydroxyethoxy)phenyl]propane and 75% by weight of polyethylene terephthalate: Example 4) or polyethylene terephthalate (PET 100%: Example 5). In Examples 4 and 5, the ratio of undegraded dye to degraded dye decreased due to the reduction in dye exhaustion caused by the decrease in copolymer content, but no significant fading occurred, and the results were satisfactory in terms of lightfastness.
[0081] [Examples 6-8, Comparative Example 5] To the copolymerized PET of Example 1, 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol] (LA31RG, manufactured by ADEKA, melting point: 197°C, molecular weight: 659) (UV absorber 1) was kneaded using a twin-screw extruder at a kneading temperature of 290°C in proportions of 0.1 wt% (Example 6), 1.0 wt% (Example 7), 4.5 wt% (Example 8), and 5.0 wt% (Comparative Example 5), then cooled and pelletized. The process was carried out according to Example 1, except that the resulting kneaded polyester was used. In Examples 6 to 8, excellent lightfastness was achieved due to the reduction in UV absorption by the UV absorber and the suppression of dye decomposition by controlling the amount of carbon radicals in the substrate. Even after the UV absorber was removed by repeated washing, excellent lightfastness was achieved due to the control of the amount of carbon radicals in the substrate.
[0082] On the other hand, in Comparative Example 5, the large amount of UV absorber added made it difficult to produce stable pellets during kneading, and furthermore, it had poor spinnability.
[0083] [Comparative Example 6] The procedure was carried out according to Example 7, except that the reducing agent concentration was changed to 4.0% owf. In Comparative Example 6, although the initial lightfastness was excellent, the lightfastness decreased due to the small molecular weight of the ultraviolet absorber, which was detached from the fibers with repeated washing.
[0084] [Comparative Example 7] The copolymerized PET of Example 1 was mixed with 2-(2-hydroxy-5-methylphenyl)benzotriazole (ADEKA, melting point: 129°C, molecular weight: 225) (UV absorber 2) at an orientation ratio of 1.0 wt% using a twin-screw extruder at a mixing temperature of 290°C, then cooled and pelletized. The process was carried out according to Example 1, except that the resulting kneaded polyester was used and the reducing agent concentration was changed to 4.0% owf. In Comparative Example 7, although the initial lightfastness was excellent, the lightfastness decreased significantly due to the detachment of the UV absorber from the fibers after repeated washing, as it was due to the low molecular weight of the UV absorber.
[0085] Table 1
[0086] Table 2
Claims
1. Polyester fibers with a carbon radical count of 2.0E+14 or less per gram.
2. The polyester fiber according to claim 1, which is a polyester containing a copolymer component.
Citation Information
Patent Citations
Polyester fiber excellent in light resistance
JP1995189031A
Sheet-like product
JP2000144583A
Polyester fiber
JP2023184004A